O imaginário da pandemia: Uma análise da cobertura dos números de mortes por Covid-19 no Jornal Nacional (JN) - SOUZA, Michele da Costa (2023)
The Covid-19 pandemic is a biological phenomenon, but also a symbolic construct permeated by several narratives that dispute the hegemony of meanings in the social sphere. The images of the phenomenon presented by Jornal Nacional (JN) are part of the social imaginary about the health crisis in the country. The numbers of deaths from Covid-19 were used in telejournalism to measure the impacts of the virus and illustrate the stages (or phases) of the disease during the pandemic (CALEFFI; PEREIRA, 2021). The present research aims to understand the meanings evoked by telejournalism when presenting the numbers of deaths by Covid-19. We analyzed ten editions of Jornal Nacional which have as a point of reference the number of deaths from the disease in the country: the first death, 5 thousand, 10 thousand, 50 thousand, 100 thousand, 200 thousand, 300 thousand, 400 thousand, 500 thousand and 600 thousand. The editions comprise moments of the first two temporalities (the years 2020 and 2021) of the pandemic. The JN was selected for having the highest audience in the segment. We start from the theoretical approach of the socio-anthropology of the imaginary (MAFFESOLI, 2001; 2020; SILVA, 2009; 2020; GOMES, 2017; GOMES, REZENDE, 2021). We also used the Audiovisual Materiality Analysis method (COUTINHO, 2016) to study the television news product in a complete way, preserving the unit: text+sound+image+time+editing. The corpus is composed of 45 pieces (including notes, editorials, reports, thematic frames) of the ten editions of the television news that address the theme of death by Covid-19. The telejournalistic device, as a technology of the imaginary (SILVA, 2020), plays an important role in the construction of the social imaginary because it represents, through technique, a cut of the social implications of a given moment. The pandemic was represented by the JN now as a tragedy, now as a catastrophe, now as war. We observed a change in the approach to the numbers of deaths by Covid-19 in the news. Death is ritualized in journalistic discourse, being translated into the symbolic space of numbers or personified in life stories. The television news also dramatized the pandemic, highlighting the individuality of the victims, their stories, dreams and trajectories seeking identification with the public.